Peran Dokter dalam Menangani Pelecehan Seksual pada Anak di Indonesia - Ocviyanti, Dwiana; Budiningsih, Yuli; Khusen, Denny; Dorothea, Maya (Majalah Kedokteran Indonesia, 2019)
Introduction: Sexual abuses often occur in Indonesia. In 2010-2014, data fromNational Commission for Child Protection showed that 42-62% of all violencein children were sexual abuses. Child sexual abuse usually happens in placesthat should be the safest place for children like home or schools. Child sexualabuse can occur verbally, non-verbally, or physically. Child sexual abuse mayaffect victim physically and mentally. The role of physicians in child sexualabuse cases are to provide medical care and statement for justice and to pre-vent negative impact of sexual abuse in the future